Math, asked by udayasreeudayan, 8 months ago

simplify and solve the following
linear equation
. 3(t-3)=5(2t+1)​

Answers

Answered by Anonymous
16

Given equation:

3(t-3) = 5(2t+1)

___________________

Solution:

3(t-3) = 5(2t+1)

3t-9 = 10t+5

-9-5 = 10t-3t

-14 = 7t

 \dfrac{ - 14}{7} = t

\boxed{\boxed {\sf {\red {-2 = t}}}}

___________________

Verification:

On substituting the value of t as -2 in the equation,

3(t-3) = 5(2t+1)

3(-2-3) = 5[2×(-2)+1]

3×(-5) = 5(-4+1)

-15 = 5×(-3)

-15 = -15

LHS = RHS

Hence Verified!

___________________

Final answer:

The value of t is \sf \purple {(-2)}.

Answered by shaswat8080
0

Step-by-step explanation:

given equation

3(t - 3) = 5(2t + 1)

simplify equation by solving brackets

3t - 9 = 10t + 5

solve equation

7t =  - 14

t =  \frac{ - 17}{2}

hence value of variable t is -2.

Similar questions